Pelaksanaan Rehabilitasi Sebagai Upaya Pengalihan Pemidanaan terhadap Penyalahgunaan Narkotika di IPWL Rumah Tenjo Laut Kuningan - Zeva Mahardika; Waluyadi; Ari Nurhaqi (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the urgency of rehabilitation for drug abuse victims and its implementation at the IPWL Rumah Tenjo Laut in Kuningan Regency. The study used an empirical legal method through a study of laws and regulations and interviews. The results show that rehabilitation plays a role in restoring the physical, psychological, and social conditions of victims and preventing the relapse. Rehabilitation is implemented through assessment, Motivational Interviewing (MI), Cognitive Behavioral Therapy (CBT), Therapeutic Community (TC) and social reintegration. Thirty-nine drug abusers underwent rehabilitation during the period 2023–April 14, 2026, as a form of diversion from a punishment. It is recommended that aftercare programs and post-rehabilitation monitoring be strengthened to reduce the risk of relapse.